PENGEMBANGAN MODUL DIGITAL BAHASA DAERAH TOLITOLI DI DEKOLAH DASAR KABUPATEN TOLITOLI - Moh Rudini; Haidar Hasan (Tolis Ilmiah : Jurnal Penelitian, 2026)
Regional languages are a cultural hearitage that plays a vital role in preserving the nation’s identity. The use of regional languages in Tolitoli Regency is increasingly eroding. Many young people are no longer fluent in the regional language, or even completelyun familiar with it. One reason is the lack of engaginglearning materials for the Tolitoli regional language. Relevant, and easly accessible. Elementary schools as basiceducation institutions have an important role in instilling the use of regional in studens. Therefore, in is necessary to develop Tolitoli regional language teaching modules that are in accordance with the curiculum and learning needs in elementary schools. So the development of this digital-based Tolitoli regional language modules is expected to be a strategic step to support the preservation of the Tolitoli CC regional language while enriching Tolitoli regional language learning at the elemtary school level. This study aims to develop a digital module by Tolitoli regional language edukation as an effort to preserve local culture and improve student competencies. Tolitoli regional language is one of the cultural assets that is threatened with extinction due to the lack of attention to its use among the younger generation, especially in elementary schools. This study will use Research and Development (R&D) apparoach with the ADDIE model (Analysis, Design, Development, Implementation, Evalutation) to produce digital-based modules that are relevant, interesting, and contextual in elemtary schools.